The effect of large eddies on the convective heat/mass transfer over complex terrain: Advanced theory and its validation against experimental and LES data - Zilitinkevich, S. S.; Hunt, J. C.R.; Grachev, A. A.; Esau, I. N.; Lalas, D. P.; Akylas, Evangelos; Tombrou, M.; Fairall, C. W.; Fernando, H. J.S.; Baklanov, A.; Joffre, S. M. (My University, 2005)
This paper presents a new theory of the convective heat/mass transfer. It focuses on (i) advanced treatment of turbulent mixing caused by large-scale semi-organised eddies overlooked in the classical theory and (ii) interactions between large eddies and surface roughness elements up to very high obstacles such as buildings, rocks and hills. Large-scale structures in the shear-free convective boundary layers consist of strong plumes and wider but weaker downdraughts. Close to the surface they cause local "convective winds" blowing towards the plume axes. The latter generate turbulence, in addition to its generation by the buoyancy forces, and strongly enhance turbulent fluxes of heat and other scalars. This mechanism is especially important over very rough surfaces. The proposed advanced model is validated against data from measurements over different sites and also through large-eddy simulation of convective boundary layers (CBLs) over a range of surfaces from very smooth to extremely rough. Excellent correspondence between model results, field observations and large-eddy simulations is achieved. The obtained resistance and heat/mass transfer laws are recommended for practical use in meso-scale, weather-prediction, climate and other environmental models.
Keywords: Convection; Semi-organised eddies; Surface fluxes